KEGIATAN SANGGAR SASTRA RUMAH PUISI TAUFIQ ISMAIL DALAM MENDUKUNG PERILAKU MENULIS - Fatma, Riska; Damayani, Ninis Agustini; Rusmana, Agus (Jurnal Kajian Informasi dan Perpustakaan, 2016)
This research purpose is to explain âSanggar Sastraâ activities at Rumah Puisi Taufiq Ismail in order to support behavior of writing literature among students, especially in Padang Panjang and Bukittinggi, West Sumatera. The method used is survey. Respondents in this research are twenty five senior high school students in Padang Panjang whom participate to âSanggar Sastraâ for a month. This research shows that an internal factor such as; membersâ interest and external factors; sanggar sastraâs teachers contributed to support behavior of writing literature among students. While the external factor such as the facilitation of âsanggar sastraâ not directly give an contributed to support behavior of writing literature among students.Penelitian ini bertujuan untuk menggambarkan aktivitas âSanggar Sastraâ di Rumah Puisi Taufiq Ismail dalam mendukung perilaku menulis di kalangan pelajar, Padang panjang dan Bukittinggi, Sumatera Barat. Metode yang digunakan ialah survey. Responden dalam penelitian ini ialah 25 Sekolah Menangah Atas (SMA) di Padang Panjang yang berpartisipasi di âSanggar Sastraâ setiap bulannya. Penelitian ini menunjukkan bahawa faktor internal diantaranya; ketertarikan angora dan faktor eksternal; pengajar Sanggar Sastra yang berkontribusi mendukung prilaku menulis diantara pelajar. Sedangkan faktor eksternal yakni fasilitas Sanggar Sastra tidak berkontribusi dalam memberikan dukungan prilaku menulis diantara pelajar.